Analisis Faktor-Faktor yang Mempengaruhi Jumlah Deposito Mudharabah pada Bank Syariah Mandiri yang Terdaftar di Bank Indonesia Periode 2010-2014 - Abrori, Imam; Khobsoh, Siti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
This study aims to identify and explain how the effect Inflation, Interest Rate Deposit, and Finance to Deposit Ratio Total Mudharabah deposits in Islamic banks. The method used is multiple linear regression. The object of research used in this research is PT. Bank Syariah Mandiri using secondary data from the publication of monthly financial statements starting from 2010-2014. The results showed that: The rate of inflation has a negative and significant effect on the amount of deposits Mudharabah. Furthermore, other results showed that the rate of interest did not affect positively and significantly to Total Deposit Mudharabah. While the results of Finance to Deposit Ratio has a positive and significant influence on the amount of deposits Mudharabah. The test is performed with a significance level of Î± = 0.1.